Answer:
2.04
Step-by-step explanation:
Answer:
![-9a^3b^2](https://tex.z-dn.net/?f=-9a%5E3b%5E2)
Step-by-step explanation:
Your Welcome!
True because they have the same size angles
<span>Simplifying
4(y + -3) = 6(y + 2)
Reorder the terms:
4(-3 + y) = 6(y + 2)
(-3 * 4 + y * 4) = 6(y + 2)
(-12 + 4y) = 6(y + 2)
Reorder the terms:
-12 + 4y = 6(2 + y)
-12 + 4y = (2 * 6 + y * 6)
-12 + 4y = (12 + 6y)
Solving
-12 + 4y = 12 + 6y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-6y' to each side of the equation.
-12 + 4y + -6y = 12 + 6y + -6y
Combine like terms: 4y + -6y = -2y
-12 + -2y = 12 + 6y + -6y
Combine like terms: 6y + -6y = 0
-12 + -2y = 12 + 0
-12 + -2y = 12
Add '12' to each side of the equation.
-12 + 12 + -2y = 12 + 12
Combine like terms: -12 + 12 = 0
0 + -2y = 12 + 12
-2y = 12 + 12
Combine like terms: 12 + 12 = 24
-2y = 24
Divide each side by '-2'.
y = -12
Simplifying
y = -12</span>
An expression for that would be s + 0.05s, or 1.05s.